Pengaruh Financial Stress terhadap Academic Stress pada Mahasiswa - Salsabila Nur Aulia Majid; Siti Pani Haningrum; Meilinda Syakila Rahmawati; Lucky Purwantini (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aimed to examine the relationship between financial stress and academic stress among university students and to identify differences in academic stress based on students' demographic characteristics. This study employed a quantitative correlational design. A total of 1,062 undergraduate students participated in the study and were selected using convenience sampling. The instruments used were the Financial Stress Scale and the Educational Stress Scale for Adolescents (ESSA). Data were analyzed using Spearman's rho correlation, simple linear regression, and the Kruskal-Wallis test. The findings revealed a very weak but significant positive relationship between financial stress and academic stress, indicating that higher levels of financial stress were associated with higher levels of academic stress. Financial stress contributed only a relatively small proportion of academic stress, suggesting that academic stress is a multidimensional phenomenon influenced by various internal and external factors. The comparative analysis showed no significant differences in academic stress based on parental income. However, significant differences were found based on GPA categories, scholarship status, and migration status. Students with lower GPAs, those who did not receive scholarships, and those living away from their families tended to experience higher levels of academic stress. These findings indicate that although financial stress affects academic stress, students' academic stress is largely influenced by the interaction of psychological, academic, and environmental factors.